Anthropometric profile and body composition of Irish adolescent rugby union players aged 16-18 - Delahunt, E.; Byrne, R. B.; Doolin, R. K.; McInerney, R. G.; Ruddock, C. T. J.; Green, B. S. (The Journal of Strength and Conditioning Research, 2013)
The literature suggests that one of the key determinants of success at rugby union international competitions is the anthropometric profile of players. The Irish Rugby Football Union (IRFU) long-term player development (LTPD) model is a framework designed to guide the development of the tactical, physical, and psychological domains of sporting participation. In Ireland, the Train-to-Train stage of the IRFU model is a critical stage, whereby the next developmental progression would include the transition of players into professional academies. To date, no previously published studies have examined the anthropometric profile of Irish Schools' rugby union players at the Train-to-Train stage of the IRFU model. The anthropometric profile of 136 male adolescent rugby union players at the Train-to-Train stage of the IRFU model was assessed using total-body dual-energy x-ray absorptiometry. Significant differences in height, body mass, body fat percentage, fat mass, lean mass, and fat-free mass were observed between players assigned to the forward and back units, and for specific position categorizations within each unit. Direct logistic regression revealed that body mass was a statistically significant (p < 0.01) predictor of unit position classification, with an odds ratio of 2.35, indicating that the players with a higher body mass were twice as likely to be classified as forwards. The results of this study indicate that at the Train-to-Train stage of the IRFU model, forward and back units have distinctly different anthropometric profiles. Furthermore, anthropometric differentiation also exists within specific position categorizations within each of these playing units. Thus, anthropometric profiling should be carried out on a systematic and periodic basis, because this will allow for the evaluation of the effectiveness of the implementation strategies of the IRFU model on a national basis.